Pengaruh Model Pembelajaran Kooperatif Tipe STAD terhadap Hasil Belajar IPA Kelas VII MTs - Fitri Yatus Saadah; Laily Yunita Susanti (Indonesian Journal of Mathematics and Natural Science Education, 2020)
Penelitian ini bertujuan : 1) untuk mengetahui perbedaan hasil belajar menggunakan model pembelajaran kooperatif tipe STAD dengan menggunakan model pembelajaran konvensional; 2) untuk mengetahui pengaruh yang signifikan penerapan model pembelajaran kooperatif tipe STAD terhadap hasil belajar siswa MTsN 1 Jember kelas VII pada materi Objek IPA dan Pengamatannya tahun pelajaran 2019/2020. Jenis penelitian ini adalah Quasi Experiment yang didesain menggunakan Nonequivalent Control Group Design dengan teknik pengambilan sampel menggunakan purposive sampling dan populasi seluruh siswa kelas VII MTsN 1 Jember. Selama proses pembelajaran, aktivitas siswa meningkat dan setelah perlakuan nilai rata-rata posttest kelas eksperimen lebih tinggi dari rata-rata posttest kelas kontrol. Berdasarkan analisis data dengan menggunakan uji-z pada taraf signifikansi 0,05, maka Ha diterima, artinya data dapat disimpulkan bahwa ada pengaruh yang signifikan penerapan model pembelajaran kooperatif tipe STAD terhadap hasil belajar siswa MTsN 1 Jember kelas VII pada materi Objek IPA dan Pengamatannya tahun pelajaran 2019/2020. Abstract The science learning still applies to the conventional learning model. Which is usually dominated by the teachers, and there are students who have individual characteristics/are less able to cooperate with others. It causes the low students learning outcomes. The Cooperative Learning model (STAD) type allows to be applied in the science learning at seventh grade on the subject matter of science and its observations, because the material is conceptual and procedural. This study aims: 1) to describe out the differences in learning outcomes using the STAD (Student Team Achievement Division) type cooperative learning model and using the conventional learning model; 2) to analyze out the significant influence of the implementation of the STAD type cooperative learning model to the learning outcomes of MTsN Jember 1 students in grade 7 on the Natural Sciences subject and its observations in academic year 2019/2020. This type of research was a Quasi Experiment that was designed using Nonequivalent Control Group Design with the sampling techniques using purposive sampling. The population was all 7th grade students of MTsN 1 Jember. During the learning process, the students activity increased and after the treatment, the posttest score of the experimental class was higher than the average posttest of the control class. Based on the data analysis using the z-test at a significance level of 0.05, Ha is accepted. It can be concluded that there was a significant influence on the implementation of the STAD type cooperative learning model to the student learning outcomes of MTsN 1 Jember in grade 7 on the Natural Sciences subject and its observations in academic year 2019/2020.